Dielectric sensor for in vivo tissue characterisation. Issue 3 (1st January 2013) - Hahn, C.; Noghanian, S.
Abstract : The design of a simple dielectric sensor for in vivo tissue dielectric property measurement is provided. The design is based on an impedance sensor.